Embracing Counsellor Professional Identity Work: Experiential Accounts of Transformation and Transition - Gignac, Kate; Gazzola, Nicola (Canadian Journal of Counselling and Psychotherapy, 2018)
This case study examines how counsellors navigate and negotiate the construction of their professional identity amid unfolding legislation set to regulate the helping professions. Ten counsellors—students, novice level, and experienced practitioners—were interviewed. The data were subject to analysis using a thematic network method designed by Attride- Stirling (2001) that resulted in five themes: (a) identity challenges and ensuing tensions, (b) facilitators of identity construction, (c) meaningfulness and sensemaking at the heart of identity work, (d) counsellors embracing their identity building, and (e) transmitting core elements and dimensionality of counsellor identity. Implications of the overall findings for counsellors and counsellor training are discussed.